Humoral Responses to Single-Dose BNT162b2 mRNA Vaccination in Dialysis Patients Previously Infected With SARS-CoV-2 - Speer, Claudius; Morath, Christian; Töllner, Maximilian; Buylaert, Mirabel; Göth, Daniel; Nusshag, Christian; Kälble, Florian; Schaier, Matthias; Grenz, Julia; Kreysing, Martin; Reichel, Paula; Hidmark, Asa; et al. (Frontiers in Medicine, 2021)
Seroconversion rates following infection and vaccination are lower in dialysis patients compared to healthy controls. There is an urgent need for the characterization of humoral responses and success of a single-dose SARS-CoV-2 vaccination in previously infected dialysis patients. We performed a dual-center cohort study comparing 3 different groups: 25 unvaccinated hemodialysis patients after PCR-confirmed COVID-19 (Group 1), 43 hemodialysis patients after two-time BNT162b2 vaccination without prior SARS-CoV-2 infection (Group 2), and 13 single-dose vaccinated hemodialysis patients with prior SARS-CoV-2 infection (Group 3). Group 3 consists of 7 patients from Group 1 and 6 additional patients with sera only available after single-dose vaccination. Anti-S1 IgG, neutralizing antibodies, and antibodies against various SARS-CoV-2 protein epitopes were measured 3 weeks after the first and 3 weeks after the second vaccination in patients without prior SARS-CoV-2 infection, 6 weeks after the onset of COVID-19 in unvaccinated patients, and 3 weeks after single-dose vaccination in patients with prior SARS-CoV-2 infection, respectively. Unvaccinated patients after COVID-19 showed a significantly higher neutralizing antibody capacity than two-time vaccinated patients without prior COVID-19 (median (IQR) percent inhibition 88.0 (71.5–95.5) vs. 50.7 (26.4–81.0); P=0.018). After one single vaccine dose, previously infected individuals generated 15- to 34-fold higher levels of anti-S1 IgG than age- and dialysis vintage-matched unvaccinated patients after infection or two-time vaccinated patients without prior SARS-CoV-2 infection with a median (IQR) index of 274 (151–791) compared to 18 (8–41) and 8 (1–21) (for both P<0.001). With a median (IQR) percent inhibition of 97.6 (97.2-98.9), the neutralizing capacity of SARS-CoV-2 antibodies was significantly higher in single-dose vaccinated patients with prior SARS-CoV-2 infection compared to other groups (for both P<0.01). Bead-based analysis showed high antibody reactivity against various SARS-CoV-2 spike protein epitopes after single-dose vaccination in previously infected patients. In conclusion, single-dose vaccination in previously infected dialysis patients induced a strong and broad antibody reactivity against various SARS-CoV-2 spike protein epitopes with high neutralizing capacity.